2009
DOI: 10.1080/10538710903051088
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sexually Abusive Experiences in Childhood and Adolescence Among a Community Sample of Latinas: A Descriptive Study

Abstract: This study examined the prevalence, severity, and circumstances of self-reported sexually coercive and abusive experiences in childhood and adolescence in a community sample of Latina women (N = 204) ages 18 to 34 years. Structured phone interviews were conducted in either English or Spanish. Results indicated that 35% of the women reported experiencing some form of sexual abuse; 31% of the reported perpetrators were family members, and 52% were boyfriends, friends or acquaintances. Of those who reported an ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 25 publications
5
27
1
Order By: Relevance
“…National data concerning CSA rates among Latino women, using adult retrospective studies, present rates that range between 15.4% and 32.1% depending on the criteria that are used to define CSA (Vogeltanz et al, 1999). In some college sample studies that have focused specifically on Latino women (Clemmons et al, 2003) or compared them to their non-Latino counterparts (Arroyo et al, 1997;Clemmons et al, 2003;Kalof, 2000;Romero, Wyatt, Loeb, Carmona, & Solis, 1999;Ullman & Filipas, 2005;Urquiza & Goodlin-Jones, 1994;Vera et al, 2005) reported rates of CSA ranged between 26% and 38%, which is consistent with CSA rates from community samples (Ulibarri, Ulloa, & Camacho, 2009). Due to methodological variation and definitional discrepancies, CSA rates among Latino women are very disparate.…”
Section: Sexual Victimizationsupporting
confidence: 54%
“…National data concerning CSA rates among Latino women, using adult retrospective studies, present rates that range between 15.4% and 32.1% depending on the criteria that are used to define CSA (Vogeltanz et al, 1999). In some college sample studies that have focused specifically on Latino women (Clemmons et al, 2003) or compared them to their non-Latino counterparts (Arroyo et al, 1997;Clemmons et al, 2003;Kalof, 2000;Romero, Wyatt, Loeb, Carmona, & Solis, 1999;Ullman & Filipas, 2005;Urquiza & Goodlin-Jones, 1994;Vera et al, 2005) reported rates of CSA ranged between 26% and 38%, which is consistent with CSA rates from community samples (Ulibarri, Ulloa, & Camacho, 2009). Due to methodological variation and definitional discrepancies, CSA rates among Latino women are very disparate.…”
Section: Sexual Victimizationsupporting
confidence: 54%
“…In addition, the cultural influence of familism may be a contributing factor in Latinas' decision to report or ability to report incidences of DV (Edelson, et al, 2007;Ulibarri, Ulloa, & Camacho, 2009;Vidales, 2010). On one hand, familism may serve as a protective factor for the victim as she reaches out for emotional support.…”
Section: Understanding Empowermentmentioning
confidence: 99%
“…; Ullrich & Lutgendorf, 2002); (e) previous history of disclosure and responses to disclosure (Ahrens, 2006); and (f) history of child sexual abuse (CSA) or other betrayal trauma (Freyd, Klest, & Allard, 2005). Other factors that might be important are current psychological functioning (clinical vs. normal) of the discloser (Smyth, 1998), type of trauma being disclosed (e.g., acute or chronic, degree of associated stigma), timing and detail of disclosure (Ullman, 1996), length of time since the trauma, gender of the disclosure recipient if there is one (Ahrens & Campbell, 2000), and (Ulibarri, Ulloa, & Camacho, 2009). These factors that can impact the outcomes of disclosure are discussed in this article in the context of studies that have examined them, although few studies have done so to date.…”
Section: Is Disclosure Therapeutic?mentioning
confidence: 99%
“…Clearly, these findings suggest that disclosure, reactions from others, and abuse severity might all play a role in explaining differences in psychological symptomatology in sexual trauma survivors. Given that ethnicity might play a role in both disclosure, who is told, and responses from others (Ulibarri et al, 2009;Ullman & Filipas, 2005a), more research on the role of ethnicity is needed, especially related to social reactions to disclosure and their impact on recovery.…”
Section: Correlates and Effects Of Sexual Trauma Disclosure In Field mentioning
confidence: 99%